Analisis Prosedur Dan Perhitungan Jaminan Kematian Pada PT. Taspen Persero Cabang Pematangsiantar - Eve Ida Malau; Eka Pratiwi Septania Parapat; Debora Silvia Hutagalung (SEKOLAH TINGGI AKUNTANSI DAN MANAJEMEN INDONESIA (STAMI), 2020)
Abstract Taspen (Persero) is one of the government companies engaged in services, where its implementation provides services to all retired Civil Servants in terms of managing Pension Funds and Old Age Allowances. The purpose of this study was to determine the analysis of the procedure and calculation of old age insurance at Taspen. The data collection technique used is the method of observation, interviews, and documentation. The analytical technique used is the Miles approach qualitative analysis technique. The results of the analysis carried out are PT. Taspen (Persero) Pematangsiantar Branch has provided a fairly good service to people who want to apply for Insurance Programs such as Work Accident Insurance and Death Insurance. Keywords: Operational activities, Insurance, Procedures